PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - TRYANNI TRYANNI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this study was to determine whether students' mathematical problem solving abilities using the Problem Based Learning (PBL) learning model would be higher than learning outcomes using conventional learning methods. The research method in this study is the experimental method. The sampling technique used a random sampling technique or a random data collection technique for the sample class, namely the experimental class and the control class by giving a question test in the form of an essay of 20 questions. The data requirements test used is the normality test with the Liliefors test and the homogeneity test with the ANOVA test. From the results of the calculation of the normality test, it is obtained that the data is normally distributed. From the results of the homogeneity test calculations, the data has a homogeneous variance. The data analysis technique used is Pearson Correlation. So that it can be found that the ability to solve mathematical problems of students who are taught using the Problem Based Learning (PBL) learning model is higher than the ability to solve mathematical problems in students using conventional learning models. Thus the Problem Based Learning (PBL) learning model influences students' mathematical problem solving abilities. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah kemampuan pemecahan masalah matematika siswa dengan menggunakan model pembelajaran Problem Based Learning (PBL) akan lebih tinggi daripada hasil belajar dengan metode pembelajaran konvesional. Metode penelitian dalam penelitian ini adalah metode eksperimen. Teknik pengambilan sampel menggunakan teknik random sampling atau teknik pengambilan data secara acak kepada kelas sample yakni kelas eksperimen dan kelas kontrol dengan cara memberikan tes soal berupa essay sebanyak 20 soal. Uji persyaratan data yang digunakan adalah uji normalitas dengan uji liliefors dan uji homogenitas dengan uji Anova. Dari hasil perhitungan uji normalitas diperoleh data berdistribusi normal. Dari hasil perhitungan uji homogenitas diperoleh data memiliki varians yang homogen. Teknik analisis data yang digunakan adalah Pearson Correlation . Sehingga di dapat bahwa kemampuan pemecahan masalah matematika siswa yang diajar dengan menggunakan model pembelajaran Problem Based Learning (PBL) lebih tinggi daripada kemampuan pemecahan masalah matematika pada siswa dengan menggunakan model pembelajaran konvesional. Dengan demikian model pembelajaran Problem Based Learning (PBL) berpengaruh terhadap kemampuan pemecahan masalah matematika siswa.